Evaluasi Kinerja Pelayanan Jalan Tol Jagorawi Dalam Memenuhi Kepuasan Pengguna - Fadhil, Dimas Nu'Man; Irenita, Novembriani; Ihsan, Tri Sandia Putri; Arizki, Salma (Jurnal Sistem Transportasi & Logistik, 2024)
PT Jasa Marga (Persero) a state-owned enterprise managing toll roads in Indonesia, including the Jagorawi Toll Road connecting Jakarta-Bogor-Ciawi, is responsible for maintaining and optimizing the functionality of toll roads for public benefit. Designed to reduce distance and travel time, the toll road now faces challenges such as increased vehicle volume and traffic congestion, which affect its effectiveness. This study aims to evaluate the performance of Jagorawi Toll Road services and its impact on user satisfaction. The research utilizes the Customer Satisfaction Index (CSI) to measure overall satisfaction and Index Performance Analysis (IPA) to identify key service attributes requiring prioritization. The analysis reveals that overall satisfaction with Jasamarga's service on the Jagorawi Toll Road is rated as "satisfied" with a CSI of 0.59. Key attributes needing improvement include: road and shoulder conditions, towing services, response time of road patrols, road lighting conditions, cleanliness and comfort of rest area toilets, cleanliness and condition of prayer facilities in rest areas, and the affordability of food in rest areas. The PT Jasa Marga focus on these attributes to enhance user satisfaction and overall service performance on the Jagorawi Toll Road.